Implementasi Desain Model Jaringan Komputer Pada Laboratorium SMPIT Al Kahfi Sidoarjo Untuk Penunjang Pelaksanaan Ujian Nasional Berbasis Komputer (UNBK) - Widoyoningrum, Sri; Tyas, Dyah Listianing; Saputro, Pujo Hari (Inovate, 2023)
This research is field research located at SMPIT AL Kahfi Tarik Sidoarjo so far does not yet have computer laboratory facilities connected to a local area network (LAN) network, so that SMP cannot carry out computer-based national exams (UNBK). The purpose of installing a local area network (LAN) network is a solution to solving existing problems at SMPIT Al Kahfi Tarik Sidoarjo. The method used is direct observation of the SMP and the design method uses a star topology. The results of the installation of a local area network (LAN) network at SMPIT Al Kahfi Tarik Sidoarjo as a means of supporting the implementation of the Computer-Based National Examination (UNBK) and can make it easier for students to implement UNBK. Keywords: Network, Local Area Network, Star Topology